Barriers to Household Risk Management : Evidence from India - Cole, Shawn A.; Giné, Xavier; Tobacman, Jeremy; Townsend, Robert M.; Topalova, Petia; Vickery, James (American Economic Association, 2014)
Why do many households remain exposed to large exogenous sources of nonsystematic income risk? We use a series of randomized field experiments in rural India to test the importance of price and nonprice factors in the adoption of an innovative rainfall insurance product. Demand is significantly price sensitive, but widespread take-up would not be achieved even if the product offered a payout ratio comparable to US insurance contracts. We present evidence suggesting that lack of trust, liquidity constraints, and limited salience are significant nonprice frictions that constrain demand. We suggest possible contract design improvements to mitigate these frictions.